(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Two hundred and fifty milk samples were collected from cows suffering from mastitis, these samples were tested for mycotic mastitis using culture and conventional PCR method. The results showed 116 isolates of Candida spp. were recovered with a prevalence of (46.4%),hence C. parapsilosis was the dominating species 15/116 (12.9%). Fifteen isolates (100%) belong C.parapsilosis was confirmed by PCR using a species specific primer for the 18S rRNA gene. Some randomly chose isolates of C. parapsilosis were used for detection of their hydrolytic enzymatic activity by API ZYM test and PCR. The method used to evaluate their enzymatic activity was API ZYM (BioMerieux). The highest activity was observed for leucine arylamidase, acid phosphatase, naphthol-AS-BI-phosphohydrolase and ?-glucosidase as 10/10 (100%) for each, followed by esterase lipase (C8) 9/10 (90%), valine arylamidase and alkaline phosphatase 8/10 (80%) for both and esterase (C4) 7/10 (70%). Conventional PCR was done for partial amplification of sterol esterase, alkaline phosphates and alpha-glucosidase genes by specific primer sequences, The results of the PCR amplification of these genes was 8/10 (80%) for sterol esterase gene. Concerning the alkaline phosphatase gene, it was present in 10/10 (100%). Regarding alpha-glucosidase gene was present in 10/10 (100%). This work aims at evaluating enzymatic activities of C. parapsilosis isolated from cow’s milk with mastitis.